Keindahan kerukunan umat beragama: Memahami dan menghargai perbedaan - Nisa', Khoirun (Maliki Interdisciplinary Journal, 2024)
Every religion that exists, especially in Indonesia, teaches us to respect each other. Basically, religious people crave peace in life. In Islam, it is thaugt to respect each other and help each other without distinguishing ethnicity, religion, or culture. The concept of tolerance in Islam contains the values of love, justice, and wisdom. With tolerance, humsns are expected to be able to form a beautiful life by maintaining harmony among many diversities. This article aims to analyze the concept of religious harmony in a multicultural society. Through a qualitative approach, this article highlights the importance of interfaith dialogue, understanding of diversity, and efforts that can be made to minimize and avoid division. Through a review of several perspectives, this article aims to provide insight into the importance of interfaith harmony in order to achieve a peaceful life.